The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1158/1535-7163.mct-11-0559
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib Sensitizes (−)-Gossypol-Induced Growth Suppression in Androgen-Independent Prostate Cancer Cells via Mcl-1 Inhibition and Bak Activation

Abstract: The natural BH3-mimetic (À)-gossypol shows promising efficacy in ongoing phase II/III clinical trials for human prostate cancer. Here, we show for the first time, that treatment with (À)-gossypol and multikinase inhibitor sorafenib synergistically suppresses the growth of androgen-independent prostate cancer cells (AI-PC) in vitro and in vivo. Our data suggest that sorafenib attenuates (À)-gossypol-induced Mcl-1 upregulation in AI-PCs. In this way, it serves as a potent chemosensitizer to affect cell death. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 38 publications
1
32
1
Order By: Relevance
“…A wide range of RTKs phosphorylate STAT3 directly or via SRC kinase, and several studies have proven that blocking kinases such as KDR, PDGFRB, and ALK results in enhanced autophagy by subsequent inhibition of the STAT3 pathway (Table 3). 14,41,42,50,[74][75][76][77][78][79][80][81][82][83] Currently, several JAK-STAT inhibitors are being examined in clinical trials for cancer therapy. For example, in a phase II clinical trial to treat metastatic pancreatic cancer, ruxolitinib together with capecitabine showed a benefit for overall survival and progression-free survival compared with a placebo plus capecitabine used in second-line therapy, promoting the application of JAK-STAT inhibitors in cancer therapy.…”
Section: Implication Of Stat3-regulated Autophagy In Cancer Therapeuticsmentioning
confidence: 99%
“…A wide range of RTKs phosphorylate STAT3 directly or via SRC kinase, and several studies have proven that blocking kinases such as KDR, PDGFRB, and ALK results in enhanced autophagy by subsequent inhibition of the STAT3 pathway (Table 3). 14,41,42,50,[74][75][76][77][78][79][80][81][82][83] Currently, several JAK-STAT inhibitors are being examined in clinical trials for cancer therapy. For example, in a phase II clinical trial to treat metastatic pancreatic cancer, ruxolitinib together with capecitabine showed a benefit for overall survival and progression-free survival compared with a placebo plus capecitabine used in second-line therapy, promoting the application of JAK-STAT inhibitors in cancer therapy.…”
Section: Implication Of Stat3-regulated Autophagy In Cancer Therapeuticsmentioning
confidence: 99%
“…Protein concentrations were measured using a BCA kit. Immunoblotting analysis was performed as described previously (Lian et al, 2012). Antibodies against phospho-or total ERK1/2, phospho-or total AKT, phospho-or total GSK3beta, phospho-or total mTOR, phospho-or total S6 kinase, Atg5, Atg10, β-catenin and LC3 were purchased from Cell Signaling Technology; GAPDH and Beclin1 were from Santa Cruz Biotechnology.…”
Section: Immunoblotting Assaymentioning
confidence: 99%
“…Preparation of ultrathin sections was described previously (Lian et al, 2012). Briefly, rats were perfused and postfixed in 1% osmium tetroxide with 0.1% potassium ferricyanide.…”
Section: Transmission Electron Microscopy Analysismentioning
confidence: 99%
“…Tumor tissues were processed for western blot as described previously. 42 All animal experiments were carried out according to the protocol approved by the Third Military Medical University Guidelines for Use and Care of Animals.…”
Section: Animal Experimentsmentioning
confidence: 99%